A mediação no âmbito das relações familiares: interdisciplinaridade, critérios de aplicação prática e soluções (a experiência da justiça paulista) - Rizkallah, Ricardo José (2018)
The present work aims to analyze interdisciplinary practice of mediation as an alternative dispute resolution available to families. We work with an idea of mediation should not be positioned as a simple alternative to the traditional jurisdictional system, but to this trying to integrate itself. Therefore, the main issue of the study is the institution of family mediation in the field of Judiciary and the study of the historical evolution of families. It discusses the most relevant aspects of mediation: legal aspects, principles, mediator role and interdisciplinarity. It also presents the Brazilian legislative movement and the most controversial issues, also including civil proceedure code and its complementary methods of alternative dispute resolution methods. Although this research points out that family mediation is a privileged area for an interdisciplinary approach, the reality reveals countless challenges on a daily basis, demonstrating a need to think means of estimulating the interdisciplinary practice in the hypotheses in which mediation is effective and the solution in the resolution of family conflicts, besides the application of criteria of practical application of the alternative dispute resolution. This research is inserted in an important historical moment to mediation in Brazil, because since 2010 it has been implemented in the Brazilian Judiciary, through a public policy of proper handling of conflicts. Within this context, the research has analysed a Project named "Casa da Família" in the City of São Vicente and developed by the Court of Justice of the State of São Paulo and sought, from a quantitative and qualitative research, between 2016 and 2017, analyze the obtained results. The achievements and concerns by ways of implementating mediation were shown in this research by considering interdiciplinary mediation for its quality and predicates, and how to effectively benefit from this cultural change. It was tried to launch theoretical bases of the use of the mediation by the trait of the interdisciplinarity in the familiar conflicts